2016
DOI: 10.1186/s12879-016-1756-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of multidrug resistant bacterial organisms and Clostridium difficile in German hospitals in 2014: Results from a nationwide one-day point prevalence of 329 German hospitals

Abstract: BackgroundOne important aspect in combatting resistance to antibiotics is to increase the awareness and knowledge by epidemiological studies. We therefore conducted a German-wide point-prevalence survey for multidrug resistant bacterial organisms (MDROs) and Clostridium difficile (CD) to assess the epidemiology and structure quality of infection control in German hospitals.Method1550 hospitals were asked to participate and to report surveillance data on the prevalence of Methicillin-resistant and Vancomycin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
1
15
0
2
Order By: Relevance
“…Notable examples are the emergence of (i) extended-spectrum β-lactam (ESBL)-/fluoroquinolone-resistant Enterobacteriaceae (3MDRO) (29, 30) in health-care settings (31) and in the poultry-production chain (19,32), (ii) carbapenem-resistant Enterobacteriaceae in broilers, pigs and meat products (33,34) as well as (iii) ESBLproducing E. coli carrying mobilizable colistin resistance (mcr) genes (35). Emergence of antimicrobial resistances in ESKAPE-bacteria is often attributed with an inappropriate use of antibiotics in human and veterinary medicine (36) on September 30, 2020 by guest http://aem.asm.org/…”
Section: Downloaded Frommentioning
confidence: 99%
“…Notable examples are the emergence of (i) extended-spectrum β-lactam (ESBL)-/fluoroquinolone-resistant Enterobacteriaceae (3MDRO) (29, 30) in health-care settings (31) and in the poultry-production chain (19,32), (ii) carbapenem-resistant Enterobacteriaceae in broilers, pigs and meat products (33,34) as well as (iii) ESBLproducing E. coli carrying mobilizable colistin resistance (mcr) genes (35). Emergence of antimicrobial resistances in ESKAPE-bacteria is often attributed with an inappropriate use of antibiotics in human and veterinary medicine (36) on September 30, 2020 by guest http://aem.asm.org/…”
Section: Downloaded Frommentioning
confidence: 99%
“…Die MRSA-Prävalenz unter den Krankenhauspatienten lag mit 1,4 % etwas unter den Angaben von Studien der Vorjahre (3,4 bzw. 1,64 % [17,18]), was dem generellen Trend einer sinkenden MRSA-Prävalenz entspricht. Die durchschnittliche VRE-Prävalenz in Krankenhäusern war im Vergleich zu Hübner et al [18] [23].…”
Section: Diskussionunclassified
“…1,64 % [17,18]), was dem generellen Trend einer sinkenden MRSA-Prävalenz entspricht. Die durchschnittliche VRE-Prävalenz in Krankenhäusern war im Vergleich zu Hübner et al [18] [23]. In den Studien von Hogardt [7] sowie March et al [24] wurden auch VRE-Prävalenzen nachgewiesen, welche bei 0,4 % -vergleichbar mit dieser Studie -bzw.…”
Section: Diskussionunclassified
“…Studies involving travel- and region-specific infections have shown that MDROs are found in all regions of the globe (CDC, 2016; Falagas, Karageorgopoulos, Leptidis, & Korbila, 2013; Huebner et al., 2016; Mwanri & AlSaleh, 2014) Studies continue to show that MDRO infections such as methicillin-resistant Staphylococcus aureus (MRSA) are common in Asia, Africa, North America, and South America but are declining in areas with strict antibiotic prescriptive policies such as Europe and Scandinavia (Falagas et al., 2013; Huebner et al., 2016; Theuretzbacher, 2013).…”
Section: Introductionmentioning
confidence: 99%